2021
DOI: 10.3389/fpls.2021.786338
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Core Mechanisms Underlying Plant Aerial Architecture

Abstract: Over the last decade or so important progress has been made in identifying and understanding a set of patterning mechanisms that have the potential to explain many aspects of plant morphology. These include the feedback loop between mechanical stresses and interphase microtubules, the regulation of plant cell polarity and the role of adaxial and abaxial cell type boundaries. What is perhaps most intriguing is how these mechanisms integrate in a combinatorial manner that provides a means to generate a large var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 120 publications
1
4
0
Order By: Relevance
“…(2017) proposed that HD-ZIP III and KAN both inhibit auxin, leaving a maximum of auxin activity in the HD-ZIP III – KAN interface zone. This is consistent with the role of PIN1-auxin PAT in regulating primordia development within the initiation zone ( Reinhardt et al., 2003 ; Hakman et al., 2009 ), and auxin’s role in morphogenetic outgrowth ( Heisler, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…(2017) proposed that HD-ZIP III and KAN both inhibit auxin, leaving a maximum of auxin activity in the HD-ZIP III – KAN interface zone. This is consistent with the role of PIN1-auxin PAT in regulating primordia development within the initiation zone ( Reinhardt et al., 2003 ; Hakman et al., 2009 ), and auxin’s role in morphogenetic outgrowth ( Heisler, 2021 ).…”
Section: Discussionsupporting
confidence: 86%
“…Members of the HD-ZIP III family were shown to control SAM activity, radial patterning, and organogenesis to various extents [ 40 , 48 , 49 , 116 , 117 , 118 ]. SAM organogenesis relies on auxin accumulation in the peripheral zone (PZ) to promote organ initiation and subsequent primordium emergence [ 119 , 120 ]. PIN1-mediated transport promotes IAA accumulation at the PZ, causing the activation of ARF-dependent and -independent signaling pathways [ 32 , 121 , 122 , 123 ].…”
Section: Sam Maintenance and Organogenesismentioning
confidence: 99%
“…Given that epidermal auxin convergence points were proposed as the trigger for auxin movement into internal cells (Scarpella et al ., 2006), but recent experiments revealed that they are neither necessary or sufficient for midvein formation in Arabidopsis (Govindaraju et al ., 2020; Lavania et al ., 2021), unknown components of auxin flux mechanisms obviously exist. In this context, both experimental and modelling approaches have suggested that mechanical stresses mediated by microtubule and cellulose microfibril dynamics play a role in both UTG and WTF movement of auxin, and it is becoming increasingly clear that the significance of auxin‐driven reorientation of PIN1 proteins during leaf primordium and midvein formation needs to be reevaluated in a more complex framework than previously considered (recently discussed and reviewed in Heisler, 2021; ten Tusscher, 2021; Vernoux et al ., 2021).…”
Section: Ontogeny Of Leaf Veinsmentioning
confidence: 99%